Computer science and statistics : proceedings of the Seventeenth Symposium on the Interface, Lexington, Kentucky, March 1985 - Allen, David M. (ed.) (Amsterdam ; New York : North-Holland ; New York, N.Y. : Sole distributors for the U.S.A. and Canada, Elsevier Science Pub. Co., 1986)
This text is proceedings of the Seventeenth Symposium on the Interface, Lexington, Kentucky, March 1985
Includes bibliographies.
ijb 16/01/2019
Loans
Keywords: Mathematical statistics